Natural and artificial radionuclides in sludge, sand, granular activated carbon and reverse osmosis brine from a metropolitan drinking water treatment plant. (October 2017) - Mulas, Dani; Camacho, Antonia; Serrano, Isabel; Montes, Sergio; Devesa, Ricard; Duch, Maria Amor
Highlights: 40 K showed the highest specific activities in sludge, sand and RO brine. 238 U showed the highest specific activities in GAC. Medically-derived 131 I was quantified in sludge, sand and GAC. 238 U, 210 Pbu, 7 Be and 137 Cs showed the highest variabilities in sludges (RSD>29%). 238 U accumulation was correlated with the progressive efficiency loss in GAC.